Analysis of Service Quality and Trust on Customer Satisfaction - Sopingi, Imam; Julaiha, Julaiha (Journal of Islamic Economics Studies and Practices, 2025)
The purpose of this research is to provide an impact on the quality of Islamic-based services and the level of trust on the level of customer satisfaction at BMT Darul Falah Cukir. The research is motivated by the declining number of customers annually, indicating possible dissatisfaction. The study employed an associative quantitative approach using a questionnaire survey involving 89 respondents selected via Slovin's formula. The instruments were tested using validity, reliability, and multiple linear regression through SPSS version 27. The results revealed that both Islamic Service Quality and Trust have a partial and simultaneous positive and significant effect on customer satisfaction, with Trust being the most dominant variable. The study recommends enhancing Sharia-compliant service quality and strengthening customer trust to retain and attract more customers.